Antidumping Protection and Productivity of Domestic Firms: A firm level analysis - Jozef Konings; Hylke Vandenbussche (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2007)
We analyze the relationship between Antidumping (AD) Protection and the productivity of EU domestic firms in import-competing industries. For this purpose we identify a panel of domestic firms between 1993 and 2003 that at some point during this period are affected by AD initiations. Using a difference-in-difference approach, we find that AD measures result in improvements of measured productivity for domestic firms. Total Factor Productivity (TFP) of protected firms increases by 2% in the short-run and by 5% to 13% in the long-run. However, there is substantial heterogeneity across firms. The effect of protection depends on the initial 'distance-to-the-frontier firm?in the industry. While protection raises TFP of 'laggard?domestic firms, it lowers TFP for 'efficient?firms that operate close to the efficiency frontier. These results are consistent with recent theoretical work supporting the view that trade policy, under certain conditions, can induce technological catching-up. While this paper evaluates the effectiveness of AD policy it does not engage in a welfare analysis.
Keywords: F13; L41; O30; C2; 330; Total Factor Productivity; Antidumping protection; technological catching-up; Antidumping; Protektionismus; Unternehmenserfolg; Produktivität; Technischer Fortschritt